Wearable Technologies 2018
DOI: 10.5772/intechopen.75483
|View full text |Cite
|
Sign up to set email alerts
|

A Proposal for New Algorithm that Defines Gait-Induced Acceleration and Gait Cycle in Daily Parkinsonian Gait Disorders

Abstract: We developed a new device, the portable gait rhythmogram (PGR), to record up to 70 hrs of movement-induced accelerations. Acceleration values induced by various movements, averaged every 10 min, showed gamma distribution, and the mean value of this distribution was used as an index of the amount of overall movements. Furthermore, the PGR algorithm can specify gait-induced accelerations using the pattern-matching method. Analysis of the relationship between gait-induced accelerations and gait cycle duration mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
(150 reference statements)
0
1
0
Order By: Relevance
“…The gait acceleration amplitude is a novel gait parameter that can be computed with the tri-axial accelerometer. A study using a force plate system showed that gait acceleration amplitude correlated with floor reaction forces [21]. Previous studies also described a lower gait acceleration amplitude in patients with early-stage PD, compared with normal subjects [8].…”
Section: Discussionmentioning
confidence: 95%
“…The gait acceleration amplitude is a novel gait parameter that can be computed with the tri-axial accelerometer. A study using a force plate system showed that gait acceleration amplitude correlated with floor reaction forces [21]. Previous studies also described a lower gait acceleration amplitude in patients with early-stage PD, compared with normal subjects [8].…”
Section: Discussionmentioning
confidence: 95%